Belief Control as Mediator Between Environmental Strategy and Eco-Practices in South Sulawesi Firms - Muhammad Try Dharsana; Nur Hazimah Alimuddin; Andi Tenri Harahap; Naufal Muhammad Aksah; Muhaizam Musa (Hasanuddin Economics and Business Review, 2025)
Departing from eco-control and competitive environmental strategy research that foregrounds diagnostic controls and advanced-economy settings, this study positions beliefs control as the mechanism translating environmental intent into practice within provincial manufacturing shaped by Indonesia’s PROPER public disclosure and Green Industry certification. A cross-sectional survey of 125 managerial respondents (operations, production, marketing, sustainability) from multi-sector manufacturing firms in South Sulawesi, Indonesia, analysed via PLS-SEM, tests mediation and predictive relevance. Beliefs control strongly predicts eco-marketing (β = 0.76, p < 0.001) and eco-production (β = 0.74, p < 0.001) and mediates the effect of eco-efficiency intent on both practices (indirect β ≈ 0.42 and 0.40, p < 0.05); the path from eco-branding intent to beliefs control is not significant (β = 0.24, p = 0.24). Explained variance is high (R² = 0.68, 0.71, 0.64). Codifying purpose through mission statements, leadership communication, and recognition systems offers an actionable route to accelerate credible eco-practices, strengthen compliance, and support cost discipline and competitive positioning. Situated in Indonesian manufacturing and in developing-region conditions, the evidence informs managerial decision-making and environmental governance in emerging markets.